Physiology of quantal norepinephrine release from somatodendritic sites of neurons in locus coeruleus - Huang, Hongping; Zhu, Fei-Peng; Chen, Xiaowei; Xu, Zhiqing David; Zhang, Claire Xi; Zhou, Zhuan (Frontiers in Molecular Neuroscience, 2012)
Norepinephrine(NE) released from the nerve terminal of locus coeruleus (LC) neurons contribute to about 70% of the total extracellular NE in primates brain.Compared with acetylcholine, glutamate, or gamma-aminobutyric acid release in neural synapses, quantal norepinephrine (NE) release from soma of LC neurons has the characteristics of long latency, nerve activity-dependency, and autoinhibition by α2-adrenergic autoreceptor. The distinct kinetics of stimulus-secretion coupling in somata are regulated by action potential patterns. The physiological significance of soma and dendritic release is to produce negative feedback and to down-regulate neuronal hyperactivity, which consequently inhibit NE release from axon terminal of LC projecting to many brain areas. Recent discoveries about the LC somatodendritic release may provide new insights into the pathogenesis of clinic disease involving LC-NE system dysfunction, and may help developing remedy targeted to the LC area.